2006
DOI: 10.1002/bem.20268
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of the effect of extremely low frequency pulsed electromagnetic fields on humans' heart rate variability

Abstract: The question whether pulsed electromagnetic field (PEMF) can affect the heart rhythm is still controversial. This study investigates the effects on the cardiocirculatory system of ELF-PEMFs. It is a follow-up to an investigation made of the possible therapeutic effect ELF-PEMFs, using a commercially available magneto therapeutic unit, had on soft tissue injury repair in humans. Modulation of heart rate (HR) or heart rate variability (HRV) can be detected from changes in periodicity of the R-R interval and/or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…This periodic component of HR is known as heart rate variability (HRV). HRV can be further demarcated into diVerent frequency components when the spectral density of the R-R intervals (intervals between successive upward deXections of the ECG arising from ventricular activation) is analyzed through Fourier transformation (Baldi et al 2007). It has been argued that a low frequency component (0.04-0.15 Hz) represents autonomic nervous system (ANS) control through aVerent sympathetic nerve activation, while parasympathetic or vagal aVerents are responsible for a high frequency (0.15-0.4 Hz) component (Baldi et al 2007).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…This periodic component of HR is known as heart rate variability (HRV). HRV can be further demarcated into diVerent frequency components when the spectral density of the R-R intervals (intervals between successive upward deXections of the ECG arising from ventricular activation) is analyzed through Fourier transformation (Baldi et al 2007). It has been argued that a low frequency component (0.04-0.15 Hz) represents autonomic nervous system (ANS) control through aVerent sympathetic nerve activation, while parasympathetic or vagal aVerents are responsible for a high frequency (0.15-0.4 Hz) component (Baldi et al 2007).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Evidence for electrophysiological effects comes from heart rate variability (HRV) studies. Baldi et al (2007) in a pilot study showed that HRV could be affected by the transition from exposed to non-exposed condition generated by a 3 Hz square wave modulation of a 50 Hz signal. Here the fi eld level was small (~5 µT) at the level of the heart, but coming from a source of 1.6 mT at fl oor level.…”
Section: Power Frequencymentioning
confidence: 99%
“…Tabor's time-domain HRV parameters included linear and non-linear analysis. Baldi et al [5] study on the influence of ELF PEMF exposure on the HRV using linear anlaysis, revealed a HR variation in all subjects.…”
Section: Introductionmentioning
confidence: 98%
“…In the past few decades, the responses of human and animal EEG activity to non-ionising radiation of Extremely Low Frequency (ELF) have been studied [2]- [5]. Since that time, various studies have reported that humans and animals are particularly sensitive to ELF or ELF modulated sensory stimulation.…”
Section: Introductionmentioning
confidence: 99%